Barriers and challenges to sustainable physical planning for mountain destinations and second-home developments in the mountain region of south-eastern Norway: the reign of governments or developers? - Tjørve, Even; Tjørve, Kathleen M. C.; Owusu, Kelvin (European Spatial Research and Policy, 2024)
The number of hotels in the mountains of south-eastern Norway has decreased over the last three decades, with a concurrent increase in the number of modern, privately-owned second homes. The growth of second-home villages and associated commercial activity has produced sustainability issues. The shift in the planning and development process from the local government to private developers has resulted in a piece-by-piece process with the loss of sight of long-term consequences. This short review discusses the causes of uncontrolled or poor planning of mountain regions; in particular, the neoliberal trend in physical planning and the problem of small local communities.